Highly active and highly selective copper extrusion catalyst

A hydrogenation catalyst composed of copper oxide, an alkali metal, and acid-stabilized silica addresses the challenges of high-pressure processes and catalyst fouling by providing high activity and selectivity at lower pressures, thus enhancing operational efficiency and safety.

JP7661223B2Active Publication Date: 2025-04-14BASF CORPORATON
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2021531596
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2018-12-03
Filing Date
2019-11-25
Publication Date
2025-04-14
Estimated Expiration
2039-11-25

Smart Images

  • Figure 0007661223000024
    Figure 0007661223000024
  • Figure 0007661223000025
    Figure 0007661223000025
  • Figure 0007661223000026
    Figure 0007661223000026
Patent Text Reader

Abstract

The hydrogenation catalyst comprises copper oxide, an alkali metal, and acid-stabilized silica, and the hydrogenation catalyst has a concentration of about 15 m 2 / g or greater Brunauer-Emmett-Teller ("BET") surface area. The hydrogenation catalyst is effective for converting aldehydes, ketones, and esters to alcohols and / or diesters to diols.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims the benefit of and priority to U.S. Provisional Application No. 62 / 774,609, filed December 3, 2018, the contents of which are incorporated herein by reference in their entirety.

[0002] The present technology relates to catalysts useful as hydrogenation catalysts, more specifically, catalysts useful for hydrogenating ketone compounds to form alcohols. The present invention also relates to methods for preparing such catalysts and the use of such catalysts in hydrogenation reactions. [Background technology]

[0003] Hydrogenation is a chemical reaction involving the addition of hydrogen (H2) and is used in large-scale industrial processes or small-scale laboratory procedures. Copper is a known catalyst for hydrogenation reactions. For example, U.S. Pat. No. 6,049,008 (Roberts) relates to chromium-free copper catalysts. For example, U.S. Pat. No. 5,124,295 (Nebesh) relates to copper chromite catalysts. An exemplary carbonyl is a ketone, such as acetophenone, which can be hydrogenated to form phenylethanol, an industrially useful feedstock, according to the hydrogenation reaction (1). [ka]

[0004] Many current commercial processes operate at high pressures, for example in the range of 75-80 bar, to convert acetophenone to phenylethanol. There is a desire to operate such processes at lower pressures in fixed bed reactors for lower operating costs and higher safety measures. Furthermore, there is a need to provide catalysts that exhibit at least the same activity and selectivity, if not better than, conventional copper-chromium catalysts. For example, the undesired reaction shown in reaction (2) results in by-products that cause fouling of the catalyst and reactor. Reaction (2) shows the dehydration of alcohols to olefins followed by hydrogenation to hydrocarbons. [ka]

[0005] There is a continuing need to provide chromium-free catalysts that maximize the desired hydrogenation products while eliminating the formation of by-products. It is also desirable to provide hydrogenation catalysts that exhibit higher catalytic activity than existing catalysts, as well as methods for their manufacture and use. Summary of the Invention

[0006] In one embodiment, a hydrogenation catalyst is provided that includes copper oxide, an alkali metal, and an acid-stabilized silica, the hydrogenation catalyst having a molecular weight of about 15 ml. 2 / g or greater Brunauer-Emmett-Teller ("BET") surface area.

[0007] In one aspect, a method of making a catalyst is provided, the method including: mixing copper oxide and a clay material to obtain a dry material mixture; combining the dry material mixture with an acid-stabilized aqueous silica solution, a caustic material, and water to obtain a wet material mixture; and calcining the wet material mixture at a temperature and for a time sufficient to harden the wet material mixture to form a calcined hydrogenation catalyst, wherein the calcined hydrogenation catalyst has a mass of about 45 m. 2 / g or more, and the pH of the acid-stabilized silica solution is less than about 3.5.

[0008] In another aspect, the present technology provides a catalyst for hydrogenation, as prepared by the method described herein in any embodiment.

[0009] In one aspect, a method for hydrogenating a ketone or aldehyde is provided, the method comprising contacting the ketone with a hydrogenation catalyst, as described herein in any embodiment.

[0010] In another aspect, a method for synthesizing butanediol is provided, the method comprising contacting a stream of dimethyl maleate with a hydrogenation catalyst, as described herein in any embodiment.

[0011] In one aspect, a method for hydrogenating an ester is provided, the method comprising contacting the ester with a hydrogenation catalyst, as described herein in any embodiment. [Brief description of the drawings]

[0012] [Figure 1] 1 illustrates a graph showing the effect of calcination temperature (° C.) on crush strength (lb / mm) of exemplary catalysts 1A-1D. [Diagram 2] 1 is a graph illustrating the effect of calcination temperature (° C.) on packed bulk density (g / ml) of exemplary catalysts 1A-1D. [Diagram 3] 1 illustrates a graph showing the effect of calcination temperature (° C.) on BET surface area (m2 / g) of exemplary catalysts 1A-1D. [Figure 4] 1 illustrates a graph showing cumulative intrusion ("pore volume", mg / L) as a function of pore size (Å) for exemplary catalysts 1A-1D. [Diagram 5] 1 illustrates a graph showing the X-ray powder diffraction spectra of exemplary catalysts 1A-1D. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] Various embodiments are described below. It should be noted that the specific embodiments are not intended as exhaustive descriptions or as limitations to the broader aspects discussed herein. An aspect described in connection with a particular embodiment is not necessarily limited to that embodiment and can be implemented in any other embodiment.

[0014] As used herein, "about" will be understood by those of ordinary skill in the art and will vary to some extent depending on the context in which it is used. If there are any uses of the term that are not clear to persons of ordinary skill in the art, "about" will mean up to ±10% of the particular term, given the context in which it is used.

[0015] The use of the terms "a" and "an" as well as "the" and similar referents in the context of describing elements (particularly in the context of the claims below) should be construed to encompass both the singular and the plural, unless otherwise indicated herein or clearly contradicted by context. The recitation of ranges of values ​​herein is intended only to serve as a shorthand method of referring individually to each individual value falling within the range, unless otherwise indicated herein, and each individual value is incorporated herein as if it were individually recited herein. All methods described herein can be performed in any suitable order, unless otherwise indicated herein or clearly contradicted by context. The use of any and all examples or illustrative language (e.g., "such as") provided herein is intended merely to better clarify the embodiments and does not limit the scope of the claims, unless otherwise indicated. No language in this specification should be construed as indicating any non-claimed element as essential.

[0016] In general, "substituted" refers to an alkyl, alkenyl, cycloalkyl, or aryl group (e.g., an alkyl group) as defined below, in which one or more bonds to a hydrogen atom contained therein are replaced by a bond to a non-hydrogen or non-carbon atom. Substituents also include groups in which one or more bonds to a carbon or hydrogen atom are replaced by one or more bonds, including double or triple bonds to a heteroatom. Thus, a substituent is substituted with one or more substituents, unless otherwise specified. In some embodiments, a substituent is substituted with 1, 2, 3, 4, 5, or 6 substituents. Examples of substituents include halogens (i.e., F, Cl, Br, and I), hydroxyl, alkoxy, alkenoxy, alkynoxy, aryloxy, aralkyloxy, heterocyclyloxy, and heterocyclylalkoxy groups, carbonyl (oxo), carboxyl, esters, urethanes, oximes, hydroxylamines, alkoxyamines, aralkoxyamines, thiols, sulfides, sulfoxides, sulfones, sulfonyls, sulfonamides, amines, N-oxides, hydrazines, hydrazides, hydrazones, azides, amides, ureas, amidines, guanidines, enamines, imides, isocyanates, isothiocyanates, cyanates, thiocyanates, imines, nitro groups, nitriles (i.e., CN), and the like.

[0017] As used herein, "alkyl" groups include straight-chain and branched alkyl groups having 1 to about 20 carbon atoms, typically 1 to 12 carbons, or in some embodiments 1 to 8 carbon atoms. As employed herein, "alkyl group" includes cycloalkyl groups as defined below. The alkyl groups may be substituted or unsubstituted. Examples of straight-chain alkyl groups include methyl, ethyl, n-propyl, n-butyl, n-pentyl, n-hexyl, n-heptyl, and n-octyl groups. Examples of branched alkyl groups include, but are not limited to, isopropyl, sec-butyl, t-butyl, neopentyl, and isopentyl groups. Representative substituted alkyl groups may be substituted one or more times with, for example, amino, thio, hydroxy, cyano, alkoxy, and / or halo groups, such as F, Cl, Br, and I groups. As used herein, the term haloalkyl is an alkyl group having one or more halo groups. In some embodiments, haloalkyl refers to groups per haloalkyl.

[0018] Cycloalkyl groups are cyclic alkyl groups such as, but not limited to, cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl, cycloheptyl, and cyclooctyl groups. In some embodiments, cycloalkyl groups have 3 to 8 ring members, while in other embodiments, the number of ring carbon atoms ranges from 3 to 5, 6, or 7. Cycloalkyl groups can be substituted or unsubstituted. Cycloalkyl groups further include polycyclic cycloalkyl groups, such as, but not limited to, norbornyl, adamantyl, bornyl, camphenyl, isocamphenyl, and carenyl groups, as well as fused rings, such as, but not limited to, decalinyl. Cycloalkyl groups also include rings substituted with straight or branched chain alkyl groups as defined above. Representative substituted cycloalkyl groups may be mono- or multiply substituted, such as, but not limited to, 2,3-, 2,4-, 2,5-, or 2,6-disubstituted cyclohexyl groups or mono-, di-, or tri-substituted norbornyl or cycloheptyl groups, which may be substituted, for example, with alkyl, alkoxy, amino, thio, hydroxy, cyano, and / or halo groups.

[0019] Alkenyl groups are straight-chain, branched, or cyclic alkyl groups having from 2 to about 20 carbon atoms and further containing at least one double bond. In some embodiments, alkenyl groups have from 2 to 12 carbons, or typically from 2 to 8 carbon atoms. Alkenyl groups can be substituted or unsubstituted. Alkyl groups include, for example, vinyl, propenyl, 2-butenyl, 3-butenyl, isobutenyl, cyclohexenyl, cyclopentenyl, cyclohexadienyl, butadienyl, pentadienyl, and hexadienyl, among others. Alkenyl groups can be substituted in the same manner as alkyl groups. Divalent alkenyl groups, i.e., alkenyl groups having two points of attachment, include, but are not limited to, CH-CH=CH2, C=CH2, or C=CHCH3.

[0020] As used herein, an "aryl" or "aromatic" group is a cyclic aromatic hydrocarbon that does not contain heteroatoms. Aryl groups include monocyclic, bicyclic, and polycyclic ring systems. Thus, aryl groups include, but are not limited to, phenyl, azulenyl, heptalenyl, biphenylenyl, indacenyl, fluorenyl, phenanthrenyl, triphenylenyl, pyrenyl, naphthacenyl, chrysenyl, biphenyl, anthracenyl, indenyl, indanyl, pentalenyl, and naphthyl groups. In some embodiments, aryl groups contain 6-14 carbons, and in other embodiments, 6-12, or even 6-10 carbon atoms in the ring portion of the group. The phrase "aryl group" includes groups that contain fused rings, such as fused aromatic aliphatic ring systems (e.g., indanyl, tetrahydronaphthyl, etc.). Aryl groups can be substituted or unsubstituted.

[0021] Reference to a transition metal component means the material used to deliver the metal, e.g., metal oxide, which may be in solid or particulate form. Thus, copper, manganese, zinc, nickel, cobalt, and / or iron may be delivered by their respective oxides.

[0022] Reference to an "alkali metal component" or an "alkaline earth metal component" means the material used to deliver the alkali metal or alkaline earth metal, for example the metal hydroxide or carbonate, which may be in powder form or as an aqueous solution.

[0023] Reference to "inorganic matrix component" means a material suitable for binding components together to form a catalyst of a certain shape. Generally, the inorganic matrix component is extrudable and used to form an extruded catalyst, and / or the inorganic matrix component can form a tableted catalyst. Thus, the inorganic matrix component or binder material may include silica, zinc oxide, zirconium oxide, clays such as bentonite, silicates such as calcium silicate, and mixtures thereof. In a preferred embodiment, the silica source is a silica sol. Suitable clays include attapulgite.

[0024] All references to pore size and pore volume in the specification and claims of this application are based on measurements using mercury porosimetry. A typical method is described in R. Anderson, Experimental Methods in Catalytic Research, Academic Press, New York, 1968. Pore volume is determined using the oxide form of the catalyst. That is, the pore size and pore volume reported herein are obtained for the catalyst after calcination but before reduction of the oxide. Those skilled in the art often refer to catalysts containing metal oxides as the "oxide" or "oxide precursor" forms of the catalyst.

[0025] The catalyst of the present technology is based on high Brunauer-Emmett-Teller ("BET") surface area copper oxide and acid-stabilized silica solution. Formation of the catalyst involves mixing and extrusion of precursor materials, followed by drying and calcination. Other additives can be included in the mixture to form the catalyst.

[0026] The catalysts described herein exhibit higher catalytic hydrogenation and hydrocracking activity and are more environmentally friendly than current commercial catalysts based on copper chromium (CuCr). The catalysts can be readily adopted and used in place of CuCr catalysts for the hydrogenation of carbonyl compounds, particularly in the styrene monomer and propylene ("SMPO") process where chromium-containing catalysts are used.

[0027] The new catalyst also exhibits significant activity and selectivity for the hydrogenation of esters such as dimethyl maleate ("DMM") to the corresponding alcohols, such as butanediol ("BDO"). The reaction sequence is shown in Scheme 1 below. [ka]

[0028] The first step is the hydrogenation of DMM to dimethyl succinate (DMS), which then undergoes hydrogenolysis to form γ-butyrolactone (gBL), which can be further hydrogenated to 1,4-butanediol (BDO), in this case the desired product. Subsequent dehydration of BDO results in the formation of tetrahydrofuran (THF) and possibly traces of n-butanol (not shown). The hydrogenation catalysts described herein exhibit low packed bulk density and strong mechanical strength when compared to currently used state-of-the-art materials, which provide the additional benefits of low cost and longer catalyst life.

[0029] Hydrogenation catalysts useful for hydrogenating carbonyl compounds to form alcohols, respectively, are provided. Exemplary carbonyl compounds are ketones and aldehydes. Methods of making and using the same are also provided. These catalysts are formed from a catalytic material and an inorganic matrix component, which are processed together, for example, by extrusion or tableting, to form the catalyst. The catalytic material includes copper oxide in combination with an alkali metal component and optionally an alkaline earth metal component. The inorganic matrix component is formed from at least a silica component (e.g., silica sol). Without intending to be bound by theory, the use of an alkali metal component results in a catalyst with superior selectivity and activity for hydrogenation. Rather than using an alkali silicate, such as sodium silicate, delivering the alkali metal components, e.g., sodium hydroxide and silica sol, respectively, separately from the silica component results in a catalyst with mesopore content that promotes hydrogenation reactions and extends catalyst life.

[0030] The catalysts disclosed herein in extruded form exhibit improved crush strength as compared to extruded catalysts formed using sodium silicate as the sole source of both the alkali metal and silica.

[0031] Catalyst Composition In one embodiment, the hydrogenation catalyst comprises copper oxide, an alkali metal, and an acid-stabilized silica, and the hydrogenation catalyst has a molecular weight of about 15000. 2 / g or greater Brunauer-Emmett-Teller ("BET") surface area.

[0032] In any embodiment herein, the hydrogenation catalyst may comprise about 15 m 2 In any embodiment herein, the hydrogenation catalyst has a BET surface area of ​​greater than about 20 m 2 In any embodiment herein, the hydrogenation catalyst has a BET surface area of ​​greater than about 30 m 2 In any embodiment herein, the hydrogenation catalyst has a BET surface area of ​​greater than about 45 m 2 In any embodiment herein, the hydrogenation catalyst has a BET surface area of ​​about 15 m 2 / g~about 70m 2 In any embodiment herein, the hydrogenation catalyst may have a BET surface area of ​​about 30 m 2 / g~about 70m 2 In any embodiment herein, the hydrogenation catalyst may have a BET surface area of ​​about 45 m 2 / g~about 70m 2 For example, in any embodiment herein, the hydrogenation catalyst may have a BET surface area of ​​about 15 m 2 / g, approx. 20m 2 / g, approx. 25m 2 / g, approx. 30m 2 / g, approx. 35m 2 / g, approx. 40m 2 / g, approx. 45m 2 / g, approx. 50m 2 / g, approx. 55m 2 / g, approx. 60m 2 / g, approx. 65m 2 / g, approx. 70m 2 / g, or any range including and / or between any two of the foregoing values. In any embodiment herein, the hydrogenation catalyst has a BET surface area of ​​about 15 m 2 / g~about 70m 2 / g, approx. 30m 2 / g~about 70m 2 / g, approx. 45m 2 / g~about 65m 2 / g, approx. 45m 2 / g~about 60m 2 / g, approx. 50m 2 / g~about 60m 2 / g, or any range including and / or between any two of the aforesaid values.

[0033] In any embodiment herein, the hydrogenation catalyst comprises copper oxide in an amount of about 50.0 wt% to about 90.0 wt% by weight of the hydrogenation catalyst. Suitable amounts of copper oxide may include, but are not limited to, about 50.0 wt% to about 90.0 wt%, about 65.0 wt% to about 85.0 wt%, about 70.0 wt% to about 80.0 wt%, or any range including and / or between any two of the aforementioned values. For example, in any embodiment herein, the amount of copper oxide may include, but is not limited to, about 50.0 wt%, about 55.0 wt%, about 60.0 wt%, about 65.0 wt%, about 70.0 wt%, about 75.0 wt%, about 80 wt%, or any range including and / or between any two of the aforementioned values.

[0034] In any embodiment herein, the alkali metal may be selected from the group consisting of sodium (Na), potassium (K), rubidium (Rb), cesium (Cs), and combinations thereof, and these metals may be present in the form of a reduced metal or oxide, or as precursors to such forms, and in one or more oxidation states as discussed above. For example, in any embodiment herein, the alkali metal component may include sodium in the form of disodium oxide. In any embodiment herein, the alkali metal component is present in an amount of 0 wt.% to about 8.0 wt.% by weight of the hydrogenation catalyst. For example, in any embodiment herein, the alkali metal component can be present in an amount of about 0.01 wt.%, about 0.1 wt.%, about 1.0 wt.%, about 1.5 wt.%, about 2.0 wt.%, about 2.5 wt.%, about 3.0 wt.%, about 3.5 wt.%, about 4.0 wt.%, about 4.5 wt.%, about 5.0 wt.%, about 5.5 wt.%, about 6.0 wt.%, about 6.5 wt.%, about 7.0 wt.%, about 7.5 wt.%, about 8.0 wt.%, or any range including and / or between any two of the afore-mentioned values. In any embodiment herein, the alkali metal component may be present in an amount of from about 0% to about 8.0% by weight, from about 1% to about 6.5% by weight, from about 3.0% to about 5.0% by weight, or any range including and / or between any two of the foregoing values.

[0035] Without intending to be bound by theory, the use of an alkali metal component results in a catalyst with excellent selectivity and activity for hydrogenation. Rather than using an alkali silicate such as sodium silicate, the delivery of an alkali metal component, e.g., sodium hydroxide and silica sol, separately from the acid-stabilized silica component, results in a catalyst with mesopore content that promotes hydrogenation reactions and extends catalyst life.

[0036] In any embodiment herein, the catalytic material may further comprise an alkaline earth metal component, the alkaline earth metal being selected from magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), and combinations thereof. These metals may be present in the form of reduced metal or oxide, or as precursors to such forms, and in one or more oxidation states as discussed above. For example, in any embodiment herein, the alkaline earth metal component is calcium, in any embodiment herein, the alkaline earth metal component may comprise calcium oxide. The alkaline earth metal component may be present in an amount of about 1.0% to about 18.0% by weight. For example, in any embodiment herein, the amount of calcium oxide can be about 1.0 wt%, about 1.5 wt%, about 2.0 wt%, about 2.5 wt%, about 3.0 wt%, about 3.5 wt%, about 4.0 wt%, about 4.5 wt%, about 5.0 wt%, about 5.5 wt%, about 6.0 wt%, about 6.5 wt%, about 7.0 wt%, about 7.5 wt%, about 8.0 wt%, about 8.5 wt%, about 9.0 wt%, about 9.5 wt%, about 10.0 wt%, about 10.5 wt%, about 11.0 wt%, about 12.0 wt%, about 13.0 wt%, about 14.0 wt%, about 15.0 wt%, about 16.0 wt%, about 17.0 wt%, about 18.0 wt%, or any range including and / or between any two of the aforesaid values.

[0037] In any embodiment herein, the catalyst may further include additional metal components. Reference to a transition metal component refers to the material used to deliver the metal, e.g., metal oxide, which may be in solid or particulate form. Thus, manganese, zinc, nickel, cobalt, and / or iron may be delivered by their respective oxides. For example, in any embodiment herein, the transition metal component may include manganese, zinc, nickel, cobalt, iron, or a mixture of two or more thereof. In any embodiment herein, the transition metal component may be manganese. For example, in any embodiment herein, the transition metal component may be manganese oxide.

[0038] The transition metal component may be present in an amount of about 0 wt.% to about 5.0 wt.%, about 0.5 wt.% to about 3.0 wt.%, about 1.0 wt.% to about 2.5 wt.%, or any range including and / or between any two of the aforementioned values. For example, in any embodiment herein, the transition metal component may be present in an amount of about 0.01 wt.%, about 0.1 wt.%, about 1.0 wt.%, about 1.5 wt.%, about 2.0 wt.%, about 2.5 wt.%, about 3.0 wt.%, about 3.5 wt.%, about 4.0 wt.%, about 4.5 wt.%, about 5.0 wt.%, or any range including and / or between any two of the aforementioned values.

[0039] The hydrogenation catalyst comprises an acid-stabilized silica. In any embodiment herein, the acid-stabilized silica can have a pH of less than about 3.5. For example, in any embodiment herein, the acid-stabilized solution has a pH of less than about 3.5, less than about 3.3, less than about 2.9, less than about 2.7, less than about 2.5, or less than about 2.3. In any embodiment herein, the acid-stabilized silica can be formed from an acid-stabilized silica solution.

[0040] In any embodiment herein, the acid-stabilized silica may be present in an amount of about 5.0% by weight to about 20.0% by weight, about 10.0% by weight to about 20.0% by weight, about 12.0% by weight to about 15% by weight, or any range of amounts including and / or between any two of the aforementioned values. For example, in any embodiment herein, the silica component may be present in an amount of about 5.0% by weight, about 6.0% by weight, about 7.0% by weight, about 8.0% by weight, about 9.0% by weight, about 10.0% by weight, about 11.0% by weight, about 12.0% by weight, about 13.0% by weight, about 14.0% by weight, about 15.0% by weight, about 16.0% by weight, about 17.0% by weight, about 18.0% by weight, about 19.0% by weight, about 20.0% by weight, or any range of amounts including and / or between any two of the aforementioned values.

[0041] In any embodiment herein, the catalyst may further comprise crystalline silica. For example, in any embodiment herein, the catalyst may comprise crystalline silica in an amount of about 0% to about 1.0% by weight. Suitable amounts may include, but are not limited to, about 0.01% by weight, about 0.1% by weight, about 0.2% by weight, about 0.3% by weight, about 0.4% by weight, about 0.5% by weight, about 0.6% by weight, about 0.7% by weight, about 0.8% by weight, about 0.9% by weight, about 1.0% by weight, or any range including and / or between any two of the aforementioned values.

[0042] In any embodiment herein, the catalyst may further comprise about 0% to about 10% by weight of a clay material. In any embodiment herein, the clay material may comprise, but is not limited to, an aluminosilicate clay, such as attapulgite, sepiolite, serpentine, kaolinite, illite, pleigorskite, montmorillonite, or mixtures thereof. For example, in any embodiment herein, the clay may be an aluminosilicate. For purposes herein, the term "attapulgite" is used to mean a chain lattice type clay mineral, and includes minerals and mineral groups variously referred to in the literature as "attapulgite," "paligorskite," "sepiolite," and "hormite." Typically, clays suitable for use in the present invention contain a large amount of attapulgite. As used herein, "major amount" means and refers to the component present in the greatest amount of any of the components present.

[0043] Specifically, these catalysts contain a significant amount of mesoporosity. References to "mesoporous" or "mesopores" refer to those pores having a pore size ranging from about 150 to about 2500 angstroms (Å). For example, in any embodiment herein, the catalyst may have a pore size ranging from about 150 Å to about 2500 Å, from about 200 Å to about 2000 Å, from about 225 Å to about 1500 Å, from about 250 Å to about 1000 Å, from about 300 Å to about 800 Å, or any range including and / or between any two of the foregoing values.

[0044] In any embodiment herein, the catalyst may be 0.25 cm 3 For example, in any embodiment herein, the catalyst may have a pore volume of about 0.25 cm 3 / g, approx. 0.3cm 3 / g, approx. 0.35cm 3 / g, approx. 0.4cm 3 / g, approx. 0.45cm 3 / g, approx. 0.5cm 3 / g, approx. 0.55cm 3 / g, approx. 0.6cm 3 / g, approx. 0.65cm 3 / g, approx. 0.7cm 3 / g, approx. 0.75cm 3 / g, approx. 0.8cm 3 / g, or any range including and / or between any two of the foregoing values. For example, in any embodiment herein, the catalyst may have a pore volume of about 0.25 cm 3 / g ~ approx. 0.65cm 3 / g, approx. 0.3cm 3 / g ~ approx. 0.55cm 3 / g, approx. 0.35cm 3 / g ~ approx. 0.45cm 3 / g, or any range including and / or between any two of the foregoing values.

[0045] In any embodiment herein, the catalyst has a surface area of ​​about 0.8 g / cm 3 ~Approx. 1.5g / cm 3 For example, in any embodiment herein, the catalyst may have a packed bulk density of about 0.8 g / cm 3 , about 0.9g / cm 3 , about 1g / cm 3 , about 1.1g / cm 3 , about 1.2g / cm 3 , about 1.3g / cm 3 , about 1.4g / cm 3 , about 1.5g / cm 3 , or any range including and / or between any two of the foregoing values. In any embodiment herein, the catalyst may have a packed bulk density of about 0.8 g / cm 3 ~Approx. 1.5g / cm3 , about 0.8g / cm~about 1g / cm 3 , about 0.8g / cm 3 ~Approx. 0.95g / cm 3 or any range including and / or between any two of the foregoing values.

[0046] In any embodiment herein, the catalyst is free of or substantially free of chromium or its oxides. Moreover, the composition is typically free of chromium to reduce exposure to such materials. As used herein, the catalyst is free of such materials if their presence is in an amount that does not substantially affect the physical, chemical and catalytic properties of the composition when compared to being completely free of such materials. Preferably, if present, such materials will be present in trace amounts, but in amounts of about 1.5 wt.% or less, more preferably 0.5 wt.% or less. For example, in any embodiment herein, the phrase "substantially free of chromium" refers to less than about 1.5 wt.%, less than about 1 wt.%, less than about 0.5 wt.%, less than about 0.1 wt.%, less than about 0.01 wt.%, or 0 wt.%, based on the total weight of the catalyst.

[0047] The catalyst can be provided as a tablet or extrudate. One way to process the blend of all the components is to extrude through a shaped orifice to form an extruded catalyst body or extrudate. Other catalyst bodies can be shaped into spheres or any other convenient shape. Another way is to tablet the catalyst. For example, in any embodiment herein, the catalyst can be extruded or tableted in sizes including, but not limited to, 1 / 8"x1 / 8", 3 / 16"x3 / 16", 1 / 4"x1 / 4", 1 / 16"x1 / 16", 3 / 16"x1 / 4", 1 / 4"x1 / 16", 1 / 8"x1 / 16", 1 / 16", 1 / 16"3F (3 grooved), 1 / 8", 1 / 8"3F, 3 / 16", or 3 / 16"3-F.

[0048] In any embodiment herein, the catalyst provided in tableted or extruded form may exhibit a crush strength in an amount of about 1.5 lbs / mm to about 6.0 lbs / mm. For example, in any embodiment herein, the catalyst may exhibit a side crush strength of about 1.5 lbs / mm, about 2.0 lbs / mm, about 2.5 lbs / mm, about 3.0 lbs / mm, about 3.5 lbs / mm, about 4.0 lbs / mm, about 4.5 lbs / mm, about 5.0 lbs / mm, about 5.5 lbs / mm, about 6.0 lbs / mm, or any range including and / or between any two of the foregoing values. In some embodiments, the catalyst may exhibit a side crush strength of about 3.5 lbs / mm to about 5.0 lbs / mm.

[0049] In any embodiment herein, the catalyst may be calcined. In any embodiment herein, the catalyst is a calcined extruded catalyst.

[0050] In any embodiment herein, the catalyst may be in a non-activated form and exhibits an X-ray powder diffraction profile with 2θ peaks at 29.6°, 35.5°, 38.7°, and 58.9°. In any embodiment herein, the catalyst may be in a non-activated form and exhibits an X-ray powder diffraction profile with 2θ peaks at 26.7°, 29.6°, 35.5°, 38.7°, 58.9°, 53.4°, 68.2°, 61.6°, 66.3°, 68.0°, 72.3°, 75.1°, and 82.9°.

[0051] In any embodiment herein, the catalyst has a copper oxide crystallite size of about 60 Å to about 200 Å. For example, in any embodiment herein, the catalyst may have a copper oxide crystallite size of about 60 Å, about 65 Å, about 70 Å, about 75 Å, about 80 Å, about 85 Å, about 90 Å, about 95 Å, about 100 Å, about 105 Å, about 110 Å, about 120 Å, about 125 Å, about 130 Å, about 135 Å, about 140 Å, about 145 Å, about 150 Å, about 155 Å, about 160 Å, about 165 Å, about 170 Å, about 175 Å, about 180 Å, about 185 Å, about 190 Å, about 195 Å, about 200 Å, or any range including and / or between any two of the foregoing values. In any embodiment, the catalyst has a copper oxide crystallite size of about 70 Å to about 165 Å.

[0052] Method of preparation In one aspect, a method for producing a catalyst for hydrogenation as described herein is provided, the method comprising: mixing copper oxide and a clay material to obtain a dry material mixture; combining the dry material mixture with an acid-stabilized aqueous silica solution, a caustic material, and water to obtain a wet material mixture; and calcining the wet material mixture at a temperature and for a time sufficient to harden the mixture to form a calcined hydrogenation catalyst, wherein the calcined hydrogenation catalyst has a hardness of about 15 m. 2 / g or more, and the pH of the acid-stabilized silica solution is less than about 3.5.

[0053] The dry material mixture also includes a clay material. In any embodiment herein, the clay material may include, but is not limited to, an aluminosilicate clay, such as attapulgite, sepiolite, serpentine, kaolinite, pleugorskite, montmorillonite, and mixtures thereof. For example, in any embodiment herein, the clay may be an aluminosilicate.

[0054] The method may further include mixing a transition metal component into the dry material mixture. For example, in any embodiment herein, the transition metal component may include, but is not limited to, manganese, zinc, nickel, cobalt, iron, or a mixture of two or more thereof. The transition metal component may be in the form of a transition metal carbonate. In any embodiment herein, the transition metal component may be manganese. For example, in any embodiment herein, the manganese may be manganese carbonate.

[0055] In any embodiment herein, the method may further include mixing an alkaline earth metal component. The alkaline earth metal component may be an alkaline earth metal or a carbonate, and the alkaline earth metal is selected from magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), and combinations thereof. For example, in any embodiment herein, the alkaline earth metal component is a calcium component, and in any embodiment herein, the calcium may be calcium hydroxide.

[0056] In any embodiment herein, the method may further include mixing one or more binders, extrusion aids, or combinations thereof into the dry material mixture. Suitable binders or extrusion aids may include, but are not limited to, polymeric polysaccharides, hydroxypropyl methylcellulose, hydroxyl ethyl methylcellulose, or mixtures of two or more thereof. For example, in any embodiment herein, the binder or extrusion aid may be selected from commercially available binders or extrusion aids, including, but not limited to, Dusoplast, Methocel, Walocel, or mixtures thereof.

[0057] The method includes combining the dry material mixture with an acid-stabilized aqueous silica solution component, a caustic material, and water. In any embodiment herein, the acid-stabilized aqueous silica solution may have a pH of less than about 3.5. For example, in any embodiment therein, the acid-stabilized solution has a pH of less than about 3.5, less than about 3.3, less than about 2.9, less than about 2.7, less than about 2.5, or less than about 2.3. A preferred silica sol that is an acid-stabilized silica solution has a pH of about 2.3 to about 3.3 and a specific surface area of ​​200 m 2 / g, density about 1.2 g / mL, viscosity about 7 cP, and 34% silica (as SiO2).

[0058] In any embodiment herein, the caustic material may include, but is not limited to, an alkali metal. The alkali metal is an alkali metal hydroxide or carbonate, where the alkali metal is selected from the group consisting of sodium (Na), potassium (K), rubidium (Rb), cesium (Cs), and combinations thereof. For example, in any embodiment herein, the alkali metal may be an alkali metal hydroxide, such as sodium hydroxide.

[0059] When the dry material mixture is combined with the aqueous acid-stabilized silica, caustic material, and water, the resulting wet material mixture undergoes an exothermic reaction. Without wishing to be bound by theory, in an exemplary embodiment, an exothermic reaction between Ca(OH)2, NaOH, and SiO2 may occur during the drying step to harden the wet material matrix. This exothermic reaction is represented by the following chemical formula: Ca(OH)2+2NaOH+2SiO2→CaSiO3+Na2SiO3+2H2O.

[0060] The method includes calcining the mixture of wet materials at a temperature and for a time sufficient to harden the mixture to form a calcined hydrogenation catalyst. In any embodiment herein, the calcination may occur at a temperature of about 300° C. to about 750° C. For example, in any embodiment herein, the calcination may occur at a temperature of about 300° C., about 350° C., about 400° C., about 450° C., about 500° C., about 550° C., about 600° C., about 650° C., about 700° C., about 750° C., or any range of temperatures including and / or between any two of the foregoing values. In any embodiment herein, the calcination temperature may be about 400° C. to about 650° C., about 400° C. to about 550° C., or about 450° C. to about 500° C. In any embodiment herein, the calcination may occur for a period of time from about 0.5 hours to about 4 hours. In any embodiment, calcination can occur for about 0.5 hours, about 1 hour, about 1.5 hours, about 2 hours, about 2.5 hours, about 3 hours, about 3.5 hours, about 4 hours, or any range including and / or between any two of the foregoing values.

[0061] In any embodiment herein, the method may further include extruding or tableting the wet material mixture prior to calcination. For example, in any embodiment herein, the wet material may be extruded or tableted in sizes including, but not limited to, 1 / 8" x 1 / 8", 3 / 16" x 3 / 16", 1 / 4" x 1 / 4", 1 / 16" x 1 / 16", 3 / 16" x 1 / 4", 1 / 4" x 1 / 16", 1 / 8" x 1 / 16", 1 / 16", 1 / 16" 3F (3 grooved), 1 / 8", 1 / 8" 3F, 3 / 16", or 3 / 16" 3-F.

[0062] In any embodiment herein, the catalyst provided in tableted or extruded form may exhibit a crush strength in an amount of about 1.5 lbs / mm to about 6.0 lbs / mm. For example, in any embodiment herein, the catalyst may exhibit a side crush strength of about 1.5 lbs / mm, about 2.0 lbs / mm, about 2.5 lbs / mm, about 3.0 lbs / mm, about 3.5 lbs / mm, about 4.0 lbs / mm, about 4.5 lbs / mm, about 5.0 lbs / mm, about 5.5 lbs / mm, about 6.0 lbs / mm, or any range including and / or between any two of the foregoing values. In some embodiments, the catalyst may exhibit a side crush strength of about 3.5 lbs / mm to about 5.0 lbs / mm.

[0063] The method may further include removing at least some water from the wet material mixture prior to calcination. For example, in any embodiment herein, the removing may include drying the wet material mixture. In any embodiment herein, the removing may occur at a temperature of about 40° C. to about 150° C. For example, in any embodiment herein, the removing may occur at a temperature of about 40° C., about 50° C., about 60° C., about 70° C., about 80° C., about 90° C., about 100° C., about 110° C., about 120° C., about 130° C., about 140° C., about 150° C., or any range of temperatures inclusive of and / or between any two of the aforementioned values. For example, in any embodiment herein, the removing may occur at a temperature of about 40° C. to about 80° C., about 45° C. to about 65° C., about 50° C. to about 60° C., or any range of temperatures inclusive of and / or between any two of the aforementioned values.

[0064] In any embodiment herein, the calcined hydrogenation catalyst has a calcination rate of about 15 m 2 In any embodiment herein, the calcined hydrogenation catalyst has a BET surface area of ​​greater than about 20 m 2 In any embodiment herein, the calcined hydrogenation catalyst has a BET surface area of ​​greater than about 30 m 2 In any embodiment herein, the calcined hydrogenation catalyst has a BET surface area of ​​greater than about 45 m 2 In any embodiment herein, the calcined hydrogenation catalyst has a BET surface area of ​​greater than about 15 m 2 / g~about 70m 2 In any embodiment herein, the calcined hydrogenation catalyst may have a BET surface area of ​​about 30 m 2 / g~about 70m 2 In any embodiment herein, the calcined hydrogenation catalyst may have a BET surface area of ​​about 45 m 2 / g~about 70m 2 For example, in any embodiment herein, the calcined hydrogenation catalyst may have a BET surface area of ​​about 15 m 2 / g, approx. 20m 2 / g, approx. 25m 2 / g, approx. 30m 2 / g, approx. 35m 2 / g, approx. 40m 2 / g, approx. 45m 2 / g, approx. 50m 2 / g, approx. 55m 2 / g, approx. 60m 2 / g, approx. 65m 2 / g, approx. 70m 2 / g, or any range including and / or between any two of the foregoing values. In any embodiment herein, the calcined hydrogenation catalyst has a BET surface area of ​​about 15 m 2 / g~about 70m 2 / g, approx. 30m 2 / g~about 70m 2 / g, approx. 45m 2 / g~about 65m 2 / g, approx. 45m 2 / g~about 60m 2 / g, approx. 50m 2 / g~about 60m 2 / g, or any range including and / or between any two of the aforesaid values.

[0065] The calcined hydrogenation catalyst may have a pore size ranging from about 150 to about 2500 angstroms (Å). For example, in any embodiment herein, the calcined hydrogenation catalyst may have a pore size ranging from about 150 Å to about 2500 Å, from about 200 Å to about 2000 Å, from about 225 Å to about 1500 Å, from about 250 Å to about 1000 Å, from about 300 Å to about 800 Å, or any range including and / or between any two of the foregoing values.

[0066] In any embodiment herein, the calcined hydrogenation catalyst may have a calcination rate of 0.25 cm 3 For example, in any embodiment herein, the calcined hydrogenation catalyst may have a pore volume of about 0.25 cm / g or more. 3 / g, approx. 0.3cm 3 / g, approx. 0.35cm 3 / g, approx. 0.4cm 3 / g, approx. 0.45cm 3 / g, approx. 0.5cm 3 / g, approx. 0.55cm 3 / g, approx. 0.6cm 3 / g, approx. 0.65cm 3 / g, approx. 0.7cm 3 / g, approx. 0.75cm 3 / g, approx. 0.8cm 3 / g, or any range including and / or between any two of the foregoing values. For example, in any embodiment herein, the calcined hydrogenation catalyst may have a pore volume of about 0.25 cm 3 / g ~ approx. 0.65cm 3 / g, approx. 0.3cm 3 / g ~ approx. 0.55cm 3 / g, approx. 0.35cm 3 / g ~ approx. 0.45cm 3 / g, or any range including and / or between any two of the foregoing values.

[0067] In any embodiment herein, the calcined hydrogenation catalyst has a calcination rate of about 0.8 g / cm 3 ~Approx. 1.5g / cm 3 For example, in any embodiment herein, the calcined hydrogenation catalyst may have a packed bulk density of about 0.8 g / cm 3 , about 0.9g / cm 3 , about 1g / cm 3 , about 1.1g / cm 3 , about 1.2g / cm 3 , about 1.3g / cm 3 , about 1.4g / cm 3 , about 1.5g / cm 3, or any range including and / or between any two of the foregoing values. For example, in any embodiment herein, the calcined hydrogenation catalyst may have a packed bulk density of about 0.8 g / cm 3 ~Approx. 1.5g / cm 3 , about 0.8g / cm~about 1g / cm 3 , about 0.8g / cm 3 ~Approx. 0.95g / cm 3 or any range including and / or between any two of the foregoing values.

[0068] In any embodiment herein, the calcined hydrogenation catalyst may exhibit a crush strength in an amount between about 1.5 lbs / mm and about 6.0 lbs / mm. For example, in any embodiment herein, the calcined hydrogenation catalyst may exhibit a side crush strength of about 1.5 lbs / mm, about 2.0 lbs / mm, about 2.5 lbs / mm, about 3.0 lbs / mm, about 3.5 lbs / mm, about 4.0 lbs / mm, about 4.5 lbs / mm, about 5.0 lbs / mm, about 5.5 lbs / mm, about 6.0 lbs / mm, or any range including and / or between any two of the foregoing values. In some embodiments, the catalyst may exhibit a side crush strength between about 3.5 lbs / mm and about 5.0 lbs / mm.

[0069] In any embodiment herein, the catalyst may be in a non-activated form and exhibits an X-ray powder diffraction profile with 2θ peaks at 29.6°, 35.5°, 38.7°, and 58.9°. In any embodiment herein, the catalyst may be in a non-activated form and exhibits an X-ray powder diffraction profile with 2θ peaks at 26.7°, 29.6°, 35.5°, 38.7°, 58.9°, 53.4°, 68.2°, 61.6°, 66.3°, 68.0°, 72.3°, 75.1°, and 82.9°.

[0070] In any embodiment herein, the calcined hydrogenation catalyst has a copper oxide crystallite size of about 60 Å to about 200 Å. For example, in any embodiment herein, the calcined hydrogenation catalyst can have a copper oxide crystallite size of about 60 Å, about 65 Å, about 70 Å, about 75 Å, about 80 Å, about 85 Å, about 90 Å, about 95 Å, about 100 Å, about 105 Å, about 110 Å, about 120 Å, about 125 Å, about 130 Å, about 135 Å, about 140 Å, about 145 Å, about 150 Å, about 155 Å, about 160 Å, about 165 Å, about 170 Å, about 175 Å, about 180 Å, about 185 Å, about 190 Å, about 195 Å, about 200 Å, or any range including and / or between any two of the foregoing values. In any embodiment, the calcined hydrogenation catalyst may have a copper oxide crystallite size of from about 70 Å to about 165 Å.

[0071] In another aspect, the present technology provides a catalyst for hydrogenation, as prepared by the method described herein in any embodiment.

[0072] How to use In one aspect, a method for hydrogenating a ketone or aldehyde is provided, the method comprising hydrogenating the ketone or aldehyde by contacting the ketone or aldehyde with a hydrogenation catalyst, as described herein.

[0073] In any embodiment herein, the ketone or aldehyde is a compound of formula I: [ka] In the formula, R 1 is substituted or unsubstituted C1-C 18 Alkyl, substituted or unsubstituted C3-C8 cycloalkyl, or substituted or unsubstituted C6-C 14 and R 2 is hydrogen or a substituted or unsubstituted C1-C 18 It is an alkyl.

[0074] In any embodiment herein, R 1 is substituted or unsubstituted C1-C 12In any embodiment herein, R 1 can be a substituted or unsubstituted C1-C6 alkyl. In any embodiment herein, R 1 is a substituted or unsubstituted C6-C 14 For example, in any embodiment herein, R 1 can be phenyl, which can be optionally substituted with one or more of halogen, amine, hydroxyl, C1-C6 alkoxy, or C1-C6 alkyl. 1 can be phenyl substituted with C1-C6 alkyl.

[0075] In any embodiment herein, R 2 can be hydrogen. In any embodiment herein, R 2 can be C1-C6 alkyl. For example, in any embodiment herein, R 2 can be C1-C4 alkyl. In any embodiment herein, R 2 can be methyl. In any embodiment herein, R 1 and R 2 may each independently be:

[0076] In any embodiment herein, the method may include hydrogenation of a ketone, as described herein in any embodiment, to a resulting aldehyde or alcohol.

[0077] In any embodiment herein, the ketone or aldehyde is a phenyl alkyl ketone or aldehyde. For example, in any embodiment herein, the ketone can be a substituted or unsubstituted phenyl alkyl ketone, such as acetophenone or 1-(4-isobutylphenyl)ethanone. [ka] Hydrogenation of such ketones can lead to 1-phenylethanol and 1-(4-isobutylphenyl)ethanol, respectively.

[0078] In another aspect, a method for synthesizing butanediol is provided, the method comprising contacting a stream of dimethyl maleate with a hydrogenation catalyst, as described herein in any embodiment.

[0079] In another aspect, a method for hydrogenating an ester is provided, the method comprising hydrogenating the ester by contacting the ester with a hydrogenation catalyst described herein.

[0080] The ester may be represented by formula II: [ka] In the formula, R 3 is substituted or unsubstituted C1-C 18 may be alkyl, R 4 is hydrogen, C1-C 18 Alkyl, C2-C 18 Alkenyl, C3-C8 cycloalkyl, or C6-C 14 It may be aryl, C1-C 18 Alkyl, C2-C 18 Alkenyl, C3-C8 cycloalkyl, or C6-C 14 The aryl can be optionally substituted with a halogen, an amine, a hydroxyl, a C1-C6 alkyl, or an ester represented by formula (III): [ka] In the formula, R 5 is hydrogen, substituted or unsubstituted C1-C 18 Alkyl, substituted or unsubstituted C2-C 18 Alkenyl, substituted or unsubstituted C3-C8 cycloalkyl, or substituted or unsubstituted C6-C 14 It may be aryl.

[0081] In any embodiment herein, R 3 is substituted or unsubstituted C1-C 12In any embodiment herein, R 3 can be a substituted or unsubstituted C1-C6 alkyl. In any embodiment herein, R 3 can be a substituted or unsubstituted C1-C4 alkyl. For example, in any embodiment, R 3 can be methyl, ethyl, propyl, n-butyl, sec-butyl, or tert-butyl. 3 can be methyl. In any embodiment herein, R 4 is substituted or unsubstituted C1-C 12 In any embodiment, R 4 may be a substituted or unsubstituted C1-C6 alkyl, a substituted or unsubstituted C2-C6 alkenyl, a substituted or unsubstituted C5 or C6 cycloalkyl, or a substituted or unsubstituted C5 or C6 aryl. 4 can be a substituted or unsubstituted C1-C6 alkyl. In any embodiment herein, R 4 can be a substituted or unsubstituted C2-C6 alkenyl. For example, in any embodiment herein, R 4 may be a C2 alkenyl substituted with an ester represented by formula (III): [ka] In the formula, R 5 can be C1-C3 alkyl. In any embodiment herein, R 5 can be methyl.

[0082] The ester may be represented by formula (IV): [ka] In the formula, R 6 and R 7 are each independently hydrogen, a substituted or unsubstituted C1-C 12 Alkyl, substituted or unsubstituted C2-C 12Alkenyl, substituted or unsubstituted C3-C8 cycloalkyl, or substituted or unsubstituted C6-C 14 In any embodiment herein, R 6 and R 7 Each independently can be C1-C6 alkyl. In any embodiment herein, R 6 and R 7 may each independently be C1-C3 alkyl. The ester represented by formula (IV) may include geometric isomers, e.g., in any embodiment disclosed herein, the ester of formula (IV) may have a cis or trans configuration.

[0083] In any embodiment herein, R 3 and R 4 together form a wax ester having a total of 12 to 36 carbon atoms in the compound represented by formula (II). 18 Alkyl or C1-C 18 It may be represented by alkenyl.

[0084] The invention thus generally described will be more readily understood by reference to the following examples, which are provided by way of illustration and are not intended to be limiting of the invention. EXAMPLES

[0085] Example 1: A series of chromium-free copper catalysts with various levels of copper oxide, sodium, and surface area were prepared as follows. Copper oxide, clay, calcium hydroxide (lime), alkali metal source (sodium hydroxide), manganese oxide, and silica sol were mixed and kneaded. The mixture was then extruded in an extruder and dried at a temperature range of 55°C to 120°C. The extrudates were then calcined at 450-600°C to the desired surface area. The catalysts had the properties outlined in Table 1, where "3F" means 3-channel or 3-lobe.

[0086] As shown in Table 1, the exemplary catalysts of the present technology exhibit improved crush strength and high BET surface area. In Examples 1A-1D, the effect of calcination temperature on physical properties was evaluated. As shown in FIG. 1, the catalysts of Examples 1A-1D exhibited improved crush strength from 3.75-5.05 lb / mm at calcination temperatures of 450-600° C. FIG. 2 shows the effect of calcination temperature on the packed bulk density of the catalyst, which increases with increasing calcination temperature. Conversely, increasing the calcination temperature of the catalyst decreased the surface area (FIG. 3). As shown in FIG. 4, the exemplary catalysts 1A-1D exhibited pore volumes of about 0.25-0.4 mL / g with pore diameters ranging from 100-1000 Å.

[0087] XRD Analysis: Data for exemplary catalysts 1A-1D were collected using a PANalytical MPD X'Pert Pro diffraction system. The analysis was performed using CuK at generator settings of 45 kV and 40 mA. α A 1000 nm radiation beam was used. The optical path consisted of a 1° divergence slit, a 2° anti-scatter slit, the sample, and an X'Celerator position-sensitive detector. Each catalyst sample was prepared by first backpacking the sample into a round mount. Data collection from the round mount covered the range 10°-90° 2θ using a step scan with a step size of 0.017° 2θ and a scan speed of 0.036° 2θ / s. The X'Pert Pro HighScore program was used for phase discrimination analysis.

[0088] Monoclinic copper oxide (CuO; 00-048-1548) was the predominant phase in exemplary catalysts 1A-1D. As shown in Figure 5, an increase in the peak intensity of this phase was observed as the calcination temperature was increased. As shown below, as the calcination temperature was increased, the peak also became sharper and there was a consistent increase in crystallite size. [Table 1] As further shown in Figure 5, orthorhombic sodium silicate (Na2SiO3, 04-008-2078) is present as a minor phase with the strongest reflection (020) coinciding at 29° 2θ. Hexagonal silica (SiO2, 01-075-3165) was observed near 27° 2θ. The complete list of 2θ peaks in Figure 5 is 26.7°, 29.6°, 35.5°, 38.7°, 58.9°, 53.4°, 68.2°, 61.6°, 66.3°, 68.0°, 72.3°, 75.1°, and 82.9°. [Table 2]

[0089] Example 2: Acetophenone Hydrogenation Testing. The chromium-free copper catalyst of Example 1 was tested in a 1 inch od (0.839 inch id) x 4 foot stainless steel fixed bed downflow reactor packed with 40 cc (extrudates or tablets) of catalyst. The catalyst was packed into an equal amount of inert 28 x 48 mesh alpha-alumina granules, which served as interstitial packing. The reactor was also equipped with a 3 / 16 inch thermowell housing six thermocouples, one at the inlet and five evenly spaced throughout the catalyst bed, which was approximately 8.25 inches in length. The reactor was jacketed and heated via a recirculating oil bath.

[0090] Once loaded, the reactor was purged with 1 standard liter per minute ("slpm") N2 for approximately 30 minutes to remove air and then heated to 190° C. under N2. The catalyst was activated by introducing H2 stepwise at atmospheric pressure, starting from a low concentration, as outlined below. Step 1: 238sccmN2 at 12sccmH2 Step 2: 225sccmN2 at 25sccmH2 Step 3: 200sccmN2 at 50sccmH2 Step 4: 125sccmN2 at 125sccmH2 Step 5: 200sccmH2 Each condition was typically held for up to 1 hour or until the exotherm had adequately subsided as indicated by the bed temperature profile. Upon completion of the reduction, the temperature was reduced to 80° C. (reaction temperature) in 200 standard cubic centimeters per minute ("sccm") of hydrogen. Once the temperature stabilized at 80° C., the reactor was pressurized from atmospheric to 900 psig for approximately 2 minutes by manually throttling H2 into the reactor.

[0091] The feed consisted of 33.33 wt% acetophenone / balance ethylbenzene solvent. Activity and acetophenone conversion were measured under conditions of 900 psig pressure, 80°C temperature, and a feed rate of 36.8 g / hr. The reaction time was approximately 1 h. -1 An overall liquid hourly space velocity ("LHSV") of 1000 and a hydrogen flow rate of 267 sccm were obtained. The hydrogen:acetophenone molar ratio was approximately 7. Product samples were collected on stream every 24 hours for runs ranging from 48 hours to 96 hours. These samples were analyzed on an off-line Agilent 6890GC equipped with a DB-WAX capillary column (30 m x 0.32 mm x 0.5 μm) and a flame ionization detector. 1-Phenylethanol is the desired product, while ethylbenzene is also a by-product in addition to being a solvent for the reactants. No other products were detected in any appreciable amounts. Commercially available copper chromium-based catalysts (Comparative Catalysts 1 and 2) as well as a reference catalyst containing ammonia-stabilized silica sol (Reference) were also evaluated. The exemplary catalysts yielded the following conversions and selectivities:

[0092] The following quantities were used to evaluate catalyst performance and are defined as follows: 1. Percent Acetophenone Conversion (X)

number

number

[0093] The data in Table 2 show that the exemplary chromium-free copper catalysts of Examples 1A-1K prepared according to the methods described herein exhibited improved STY for phenylethanol yield and catalyst life compared to Comparative Catalysts 1 and 2 (commercial CuCr catalysts) and the reference catalyst (ammonia silica sol catalyst). Although the exemplary chromium-free copper catalysts of Examples 1A-1K exhibited comparable acetophenone conversion to Comparative Catalyst 2, the exemplary chromium-free copper catalysts of Examples 1A-1K exhibited higher acetophenone conversion, phenylethanol yield, and lower production of ethylbenzene by-product compared to Comparative Catalysts 1 and 2 and the reference catalyst. Additionally, the chromium-free copper catalysts of Examples 1A-1K have more stable catalytic activity, with the exemplary catalysts remaining stable over the test period (up to 96 hours) without loss of acetophenone conversion. In contrast, Comparative Catalysts 1 and 2 and the reference catalyst either exhibited lower activity or lower acetophenone conversion.

[0094] Table 3 below shows the maximum temperatures measured by any bed thermocouple during reduction and initial pressurization of the reactor for use according to Comparative Examples 1 and 2 and Example 1K. [Table 4]

[0095] As shown in Table 3, this is evidenced by the slight temperature rise from the 190° baseline temperature during reduction and the temperature rise observed during pressurization above the 80° C. baseline temperature. The catalyst of Example 1K exhibited a mild exotherm during pressurization, experiencing only a very small temperature rise of 2° C., most likely due to the heat of adsorption under pressurized conditions. In contrast, both Comparative Catalysts 1 and 2 produced sharp exotherms upon pressurization to 280° C. and 270° C., respectively. Without wishing to be bound by theory, it is believed that the sharp exotherms are related to the presence of Cr(6+) in the higher oxidation state. At large commercial scale reactor conditions, this large exotherm poses a safety risk, is dangerous, and creates operational difficulties.

[0096] Example 2: Dimethyl Maleate Hydrogenolysis Test. For the dimethyl maleate hydrolysis catalyst test, 15 cc of the chromium-free copper catalyst of Example 1 was loaded into a 1 inch OD (0.834 inch ID) x 4 ft stainless steel fixed bed downflow reactor. The catalyst was loaded into an equal amount of inert 40 x 50 mesh alpha-alumina granules, which served as interstitial packing. The reactor was also equipped with a 3 / 16 inch thermowell housing five thermocouples, two in the preheat zone and three evenly spaced throughout the approximately 3 inch long catalyst bed. The reactor was jacketed and heated via a recirculating oil bath.

[0097] Once loaded, the reactor was purged with 4 slpm N2 for approximately 30 minutes to remove air and then heated to 140° C. with flowing N2 at atmospheric pressure. Once 140° C. was reached, 20 sccm of H2 was introduced into the N2 and the catalyst was then heated to 220° C. At this point, the H2 concentration was increased in a stepwise manner as outlined below: Step 1: 40sccmH2 with 4slmpN2 Step 2: 80sccmH2 with 4slmpN2 Step 3: 160sccmH2 with 4slmpN2 Step 4: 320sccmH2 with 4slmpN2 Step 5: 640sccmH2 with 4slmpN2 Step 6: 640sccmH2 with 2slmpN2 Step 7: 640sccmH2

[0098] Each condition was typically held for about 20 minutes or until the exotherm had adequately subsided as indicated by the bed temperature profile. Once reduction was complete, the temperature was increased to 200° C., after which the reactor was pressurized to 900 psig under 20 standard liters per hour ("slph") H2 flow. Once pressurization was complete, the reactor was further cooled to 185° C. under 466.2 slph H2.

[0099] With H2 flowing at 466.2 slph and steady at 185°C and 900 psig, 100% DMM feed was pumped into the reactor at a rate of 8.6 g / hr, resulting in an overall LHSV of approximately 0.5 hr. -1 The H2:DMM molar ratio was approximately 350, which was high enough to ensure that the feed remained in the gas phase. Product samples were collected in a liquid N2 cooled trap once a day for the duration of the experiment. Samples were analyzed on an off-line Agilent 6890GC equipped with a DB-1 capillary column (30 m × 0.32 mm × 3 μm) and a flame ionization detector. In addition, the off-gas from the trap was analyzed by a 5890GC equipped with a SPB-1 capillary column (30 m × 0.32 mm × 0.1 μm) and a flame ionization detector. The off-gas typically consisted of methanol with a small amount of THF escaping from the liquid N2 trap.

[0100] The following quantities were used to evaluate catalyst performance and are defined as follows: 1. Percentage DMM Conversion (X DMM ):

number

number

number

[0101] While certain embodiments have been illustrated and described, it is to be understood that changes and modifications can be made therein by those skilled in the art without departing from the technology in its broader aspects, as defined in the following claims.

[0102] References throughout this specification to "one embodiment," "a particular embodiment," "one or more embodiments," or "an embodiment" mean that a particular feature, structure, material, or characteristic described in connection with an embodiment is included in at least one embodiment of the invention. Thus, the appearances of phrases such as "in one or more embodiments," "in a particular embodiment," "in one embodiment," or "in an embodiment" in various places throughout this specification do not necessarily refer to the same embodiment of the invention. Furthermore, the particular features, structures, materials, or characteristics may be combined in any suitable manner in one or more embodiments.

[0103] The embodiments illustratively described herein may be suitably practiced in the absence of any element or elements, any limitation or limitations not specifically disclosed herein. Thus, for example, terms such as "comprising", "including", "containing" and the like should be read expansively and not limiting. Furthermore, the terms and expressions used herein are used as terms of description and not of limitation, and there is no intention to use such terms and expressions to exclude any equivalents of the shown and described functions or portions thereof, but it is recognized that various modifications are possible within the scope of the claimed technology. Furthermore, the phrase "consisting essentially of" will be understood to include those elements specifically recited and those additional elements that do not materially affect the basic and novel characteristics of the claimed technology. The phrase "consisting of" excludes any elements not specified.

[0104] The present disclosure should not be limited with respect to the specific embodiments described in this application. As will be apparent to those skilled in the art, many modifications and variations can be made without departing from the spirit and scope thereof. In addition to those listed herein, functionally equivalent methods and compositions within the scope of the present disclosure will be apparent to those skilled in the art from the foregoing description. Such modifications and variations are intended to be within the scope of the appended claims. The present disclosure should be limited only by the terms of the appended claims, along with the full scope of equivalents to which such claims are entitled. It is to be understood that the present disclosure is not limited to specific methods, reagents, compounds, compositions, or biological systems, which can, of course, vary. It is also to be understood that the terminology used herein is for the purpose of describing particular embodiments only, and is not intended to be limiting.

[0105] In addition, when features or aspects of the disclosure are described in terms of a Markush group, those skilled in the art will recognize that the disclosure is also thereby described in terms of any individual element or subgroup of elements of the Markush group.

[0106] As will be understood by those skilled in the art, for any and all purposes, particularly in terms of providing a written description, all ranges disclosed herein also encompass any and all possible subranges and combinations of these subranges. The ranges listed are fully descriptive and can be easily recognized as being able to divide the same range into at least equal halves, thirds, quarters, fifths, tenths, etc. As a non-limiting example, each range discussed herein can be easily divided into a lower third, a middle third, and an upper third. Also, as will be understood by those skilled in the art, all terms such as "up to," "at least," "greater than," "less than," etc., refer to ranges that are inclusive of the recited numbers and can be subsequently divided into subranges as discussed above. Finally, as will be understood by those skilled in the art, a range includes each individual element.

[0107] All publications, patent applications, issued patents, and other documents referred to in this specification are incorporated herein by reference as if each individual publication, patent application, issued patent, or other document was specifically and individually indicated to be incorporated by reference in its entirety. Definitions contained in the texts incorporated by reference are excluded to the extent that they conflict with definitions in this disclosure.

[0108] Other embodiments are within the scope of the following claims.

Claims

1. A hydrogenation catalyst comprising: Copper oxide, An alkali metal, and an acid-stabilized silica, The hydrogenation catalyst is 15m 2 / g or more Brunauer-Emmett-Teller ("BET") surface area and a copper oxide crystallite size of 60 Å to 200 Å.

2. The BET surface area is 15 m 2 / g ~ 70m 2 The hydrogenation catalyst according to claim 1, wherein the hydrogenation catalyst has a molecular weight of 1.0 to 1.0 g.

3. The BET surface area is 50 m 2 / g ~ 60m 2 The hydrogenation catalyst according to claim 1 or 2, wherein the molar ratio of the hydrogen atom to the hydrogen atom is 1:1 or 1:

1.

4. 4. The hydrogenation catalyst according to claim 1, wherein the copper oxide is present in an amount of from 50.0% to 85.0% by weight based on the weight of the hydrogenation catalyst.

5. 5. The hydrogenation catalyst according to any one of claims 1 to 4, wherein the copper oxide is present in an amount of from 65.0 wt% to 80.0 wt% by weight of the hydrogenation catalyst.

6. 6. The hydrogenation catalyst according to any one of claims 1 to 5, wherein the copper oxide is present in an amount of from 70.0 wt% to 75.0 wt% by weight of the hydrogenation catalyst.

7. The hydrogenation catalyst according to any one of claims 1 to 6, wherein the alkali metal component comprises sodium.

8. The hydrogenation catalyst according to any one of claims 1 to 7, wherein the alkali metal component comprises disodium oxide.

9. The hydrogenation catalyst according to any one of claims 1 to 8, wherein the alkali metal component is present in an amount of from 0.01 wt% to 8.0 wt% by weight of the hydrogenation catalyst.

10. The hydrogenation catalyst according to any one of claims 1 to 9, wherein the alkali metal component is present in an amount of from 3.0 wt% to 5.0 wt% by weight of the hydrogenation catalyst.

11. The hydrogenation catalyst according to any one of claims 1 to 10, further comprising 1.0 wt% to 18.0 wt% calcium oxide, based on the weight of the hydrogenation catalyst.

12. The hydrogenation catalyst according to any one of claims 1 to 11, further comprising a transition metal component selected from the group consisting of manganese, zinc, nickel, cobalt, and iron.

13. The hydrogenation catalyst according to any one of claims 1 to 11, further comprising a transition metal component which is a manganese oxide.

14. 14. The hydrogenation catalyst of claim 12 or claim 13, wherein the transition metal component is present in an amount of from 0.01 wt % to 5.0 wt % by weight of the hydrogenation catalyst.

15. 15. The hydrogenation catalyst according to any one of claims 1 to 14, wherein the acid-stabilized silica is present in an amount of from 5.0 wt% to 20.0 wt% by weight of the hydrogenation catalyst.

16. 16. The hydrogenation catalyst according to any one of claims 1 to 15, wherein the acid-stabilized silica is present in an amount of from 10.0 wt% to 18.0 wt% by weight of the hydrogenation catalyst.

17. The hydrogenation catalyst according to any one of claims 1 to 16, further comprising from greater than 0 wt% to 1.0 wt% or less of crystalline silica by weight of the hydrogenation catalyst.

18. 18. The hydrogenation catalyst according to any one of claims 1 to 17, further comprising from greater than 0 to up to 10 wt% of a clay material.

19. The hydrogenation catalyst material has a thickness of ≧0.25 cm 3 The hydrogenation catalyst according to any one of claims 1 to 18, exhibiting a pore volume of 0.1 to 0.5 wt. / g.

20. The hydrogenation catalyst has a density of 0.8 g / cm 3 ~1.5g / cm 3 The hydrogenation catalyst according to any one of claims 1 to 19, exhibiting a packed bulk density of

21. The hydrogenation catalyst according to any one of claims 1 to 20, wherein the hydrogenation catalyst is free or substantially free of chromium or its oxides.

22. The hydrogenation catalyst according to any one of claims 1 to 21, wherein the hydrogenation catalyst is in the form of a solid extrudate or tablet.

23. 1. A process for preparing a calcined hydrogenation catalyst comprising the steps of: mixing copper oxide and a clay material to obtain a dry material mixture; combining the dry material mixture with an acid-stabilized aqueous silica solution, an alkali metal hydroxide, and water to obtain a wet material mixture; and calcining the wet material mixture at a temperature and for a time sufficient to harden the wet material mixture to form a calcined hydrogenation catalyst. The calcined hydrogenation catalyst is 15 m 2 / g or more and has a copper oxide crystallite size of 60 Å to 200 Å; The method wherein the pH of the acid-stabilized silica solution is less than 3.

5.

24. 24. The method of claim 23, wherein the method comprises extruding or tableting the wet material mixture prior to calcination.

25. The calcined hydrogenation catalyst is 15 m 2 ~70m 2 25. The method of claim 23 or claim 24, wherein the SiO2 has a BET surface area of ​​100 / g.

26. The calcined hydrogenation catalyst is 50 ml 2 / g to 60m 2 The method according to any one of claims 23 to 25, wherein the SiO2 has a BET surface area of ​​0.1 to 0.5 g / g.

27. The method of any one of claims 23 to 26, further comprising mixing an alkaline earth metal component with the dry material mixture.

28. 28. The method of claim 27, wherein the alkaline earth metal component is calcium hydroxide.

29. 29. The method of any one of claims 23 to 28, wherein the clay material comprises an aluminosilicate attapulgite clay.

30. 30. The method of any one of claims 23 to 29, further comprising mixing a transition metal component selected from the group consisting of manganese, zinc, nickel, cobalt, and iron into the dry material mixture.

31. The method of claim 30 , wherein the transition metal component comprises a manganese oxide.

32. The method of any one of claims 23 to 31, further comprising mixing one or more binders, extrusion aids, or a combination of any two or more thereof with the dry ingredient mixture.

33. 33. The method of claim 32, wherein the one or more binders or extrusion aids are selected from polymeric polysaccharides, hydroxypropyl methylcellulose, hydroxyethyl methylcellulose, or a mixture of two or more thereof.

34. 24. The method of claim 23, wherein the alkali metal hydroxide is sodium hydroxide.

35. The method of any one of claims 23 to 34, further comprising removing at least some water from the wet material mixture before calcining.

36. 36. The method of claim 35, wherein the removing of water is carried out at a temperature of from 40°C to 150°C.

37. 37. The method of claim 36, wherein the temperature is from 50°C to 60°C.

38. The method of any one of claims 23 to 37, wherein the method further comprises extruding the wet material mixture before calcining.

39. A process according to any one of claims 23 to 38, wherein the calcination is carried out at a temperature of from 400°C to 650°C.

40. 40. The method of claim 39, wherein the temperature is between 400°C and 550°C.

41. 41. The method of claim 40, wherein the temperature is between 450°C and 500°C.

42. 1. A process for hydrogenating a ketone or aldehyde, comprising: Copper oxide, An alkali metal component; and an acid stabilized silica; The hydrogenation catalyst is 15m 2 / g or more and has a Brunauer-Emmett-Teller ("BET") surface area of ​​60 Å to 200 Å.

43. 43. The method of claim 42, wherein the acid-stabilized silica is formed from an acid-stabilized silica solution having a pH of less than 3.

5.

44. The hydrogenation catalyst is 15m 2 / g ~ 70m 2 44. The method of claim 42 or claim 43, wherein the SiO2 has a BET surface area of ​​100 / g.

45. The hydrogenation catalyst is 50 m 2 / g to 60m 2 The method according to any one of claims 42 to 44, wherein the SiO2 has a BET surface area of ​​0.1 to 0.5 g / g.

46. 46. ​​The method of claim 45, wherein the copper oxide is present in an amount of 50.0 wt.% to 85.0 wt.% by weight of the hydrogenation catalyst.

47. The method of any one of claims 42 to 46, wherein the alkali metal component comprises sodium.

48. 48. The process of any one of claims 42 to 47, wherein the alkali metal component is present in an amount of from 0.01 wt% to 8.0 wt% by weight of the hydrogenation catalyst.

49. 49. The method of any one of claims 42 to 48, wherein the hydrogenation catalyst further comprises 1.0 wt% to 18.0 wt% calcium oxide by weight of the hydrogenation catalyst.

50. 50. The method of any one of claims 43 to 49, wherein the hydrogenation catalyst further comprises a transition metal component selected from the group consisting of manganese, zinc, nickel, cobalt, and iron.

51. 51. The method of claim 50, wherein the transition metal component is present in an amount of 0.01 wt.% to 5.0 wt.% by weight of the catalyst.

52. 52. The method of any one of claims 42 to 51, wherein the acid-stabilized silica is present in an amount of from 5.0 wt% to 20.0 wt% by weight of the catalyst.

53. The method of any one of claims 42 to 52, wherein the catalyst further comprises 0.01 wt % to 1.0 wt % crystalline silica based on the weight of the catalyst.

54. The ketone is represented by formula I: 【Chemistry 1】 During the ceremony, R 1 is a substituted or unsubstituted C 1 ~C 18 Alkyl, substituted or unsubstituted C 3 ~C 8 Cycloalkyl, or substituted or unsubstituted C 6 ~C 14 is aryl, R 2 is hydrogen, or a substituted or unsubstituted C 1 ~C 18 The method of any one of claims 42 to 53, wherein the alkyl group is alkyl.

55. R 1 is a substituted or unsubstituted C 6 ~C 14 55. The method of claim 54, wherein said is aryl.

56. R 1 56. The method of claim 54 or claim 55, wherein is substituted or unsubstituted phenyl.

57. R 1 is halogen, amine, hydroxyl, or C 1 ~C 6 57. The method of claim 56, wherein said aryl is phenyl optionally substituted with one or more of alkyl.

58. R 2 The method of claim 57, wherein is methyl.

59. 59. The method of any one of claims 43 to 58, wherein the ketone is a phenyl alkyl ketone.

60. 60. The method of claim 59, wherein the phenyl alkyl ketone is acetophenone.

61. 1. A method for synthesizing butanediol, comprising the steps of: The flow of dimethyl maleate is Copper oxide, An alkali metal component; and an acid stabilized silica; The hydrogenation catalyst is 15m 2 / g or greater Brunauer-Emmett-Teller ("BET") surface area; The method wherein the silica is formed from an acid-stabilized silica solution having a pH of less than 3.

5.

62. The hydrogenation catalyst is 15m 2 / g ~ 70m 2 62. The method of claim 61 , wherein the SiO 2 has a BET surface area of ​​100 / g.

63. The hydrogenation catalyst is 50 m 2 / g to 60m 2 63. The method of claim 61 or claim 62, wherein the SiO2 has a BET surface area of ​​100 / g.

64. 64. The method of any one of claims 61 to 63, wherein the copper oxide is present in an amount of 50.0 wt% to 85.0 wt% by weight of the hydrogenation catalyst.

65. 65. The method of any one of claims 61 to 64, wherein the alkali metal component comprises sodium.

66. 66. The process of any one of claims 61 to 65, wherein the alkali metal component is present in an amount of from 0.01 wt% to 8.0 wt% by weight of the hydrogenation catalyst.

67. 67. The method of any one of claims 61 to 66, wherein the hydrogenation catalyst further comprises 1.0 wt% to 18.0 wt% calcium oxide by weight of the hydrogenation catalyst.

68. 68. The method of any one of claims 61 to 67, wherein the hydrogenation catalyst further comprises a transition metal component selected from the group consisting of manganese, zinc, nickel, cobalt, and iron.

69. 69. The method of claim 68, wherein the transition metal component is present in an amount of 0.01% to 5.0% by weight of the catalyst weight.

70. 70. The method of any one of claims 61 to 69, wherein the acid-stabilized silica is present in an amount of 5.0 wt% to 20.0 wt% by weight of the catalyst.

71. 71. The method of any one of claims 61 to 70, wherein the hydrogenation catalyst further comprises 0.01 wt% to 1.0 wt% crystalline silica by weight of the hydrogenation catalyst.

72. 23. The hydrogenation catalyst according to any one of claims 1 to 22, wherein the hydrogenation catalyst is in a non-activated form and exhibits an X-ray powder diffraction profile with 2θ peaks at 29.6°, 35.5°, 38.7°, and 58.9°.

73. 73. The hydrogenation catalyst of claim 72, wherein the hydrogenation catalyst is in a non-activated form and exhibits an X-ray powder diffraction profile having 2θ peaks at 26.7°, 29.6°, 35.5°, 38.7°, 58.9°, 53.4°, 68.2°, 61.6°, 66.3°, 68.0°, 72.3°, 75.1°, and 82.9°.

74. 74. The hydrogenation catalyst of claim 72 or 73, wherein the hydrogenation catalyst has a copper oxide crystallite size of from 60 Å to 200 Å.

75. 75. The hydrogenation catalyst of claims 1 to 22 or 74, wherein the hydrogenation catalyst has a copper oxide crystallite size of from 70 Å to 165 Å.

76. 42. The method of any one of claims 23 to 41, wherein the hydrogenation catalyst is in a non-activated form and exhibits an X-ray powder diffraction profile with 2θ peaks at 29.6°, 35.5°, 38.7°, and 58.9°.

77. 77. The method of claim 76, wherein the hydrogenation catalyst is in a non-activated form and exhibits an X-ray powder diffraction profile with 2θ peaks at 26.7°, 29.6°, 35.5°, 38.7°, 58.9°, 53.4°, 68.2°, 61.6°, 66.3°, 68.0°, 72.3°, 75.1°, and 82.9°.

78. 80. The method of any one of claims 25 to 41 or 77, wherein the hydrogenation catalyst has a copper oxide crystallite size of from 60 Å to 200 Å.

79. 79. The method of claim 78, wherein the catalyst has a copper oxide crystallite size of from 70 Å to 165 Å.

80. 1. A process for hydrogenating an ester, comprising: Copper oxide, An alkali metal component; and an acid stabilized silica; The hydrogenation catalyst is 15m 2 / g or more and has a Brunauer-Emmett-Teller ("BET") surface area of ​​60 Å to 200 Å.

81. The ester is represented by formula II: 【Chemistry 2】 During the ceremony, R 3 is a substituted or unsubstituted C 1 ~C 18 is alkyl, R 4 is hydrogen, C 1 ~C 18 Alkyl, C 2 ~C 18 Alkenyl, C 3 ~C 8 Cycloalkyl, or C 6 ~C 14 is aryl, Said C 1 ~C 18 Alkyl, C 2 ~C 18 Alkenyl, C 3 ~C 8 Cycloalkyl, or C 6 ~C 14 Aryl is optionally selected from halogen, amine, hydroxyl, C 1 ~C 6 substituted with one or more of an alkyl, or an ester represented by formula (III): 【Chemistry 3】 In the formula, R 5 is hydrogen, substituted or unsubstituted C 1 ~C 18 Alkyl, substituted or unsubstituted C 2 ~C 18 Alkenyl, substituted or unsubstituted C 3 ~C 8 Cycloalkyl, or substituted or unsubstituted C 6 ~C 14 81. The method of claim 80, wherein said is aryl.

82. The ester is represented by formula (IV): 【Chemistry 4】 During the ceremony, R 6 and R 7 each independently represents a substituted or unsubstituted C 1 ~C 12 Alkyl, substituted or unsubstituted C 2 ~C 12 Alkenyl, substituted or unsubstituted C 3 ~C 8 Cycloalkyl, or substituted or unsubstituted C 6 ~C 14 is aryl, 82. The method of claim 80 or claim 81, wherein the ester of formula (IV) has a cis or trans configuration.

Citation Information

Patent Citations

  • Hydrogenated molding catalyst, method for producing the same, and use

    JP1999507867A

  • A copper-silica catalyst useful for hydrogenation of acarbonyl group-containing compound or dehydrogenationof a cycloalcohol and a preparation thereof

    KR1020030012738A

  • Hydrogenation catalysts

    US20160038917A1

  • Fluidizable zinc titanate materials with high chemical reactivity and attrition resistance

    US5254516A